Association of Single Nucleotide Polymorphism (rs 2108429654A/T) in PI3KCA Gene with Risk of Breast Cancer in Iraqi Women - Mutaeb, Makarem Satar; Umran, Mahfoodh Abbas; Alabboodi, Musaab Kadhim (Iraqi Journal of Science, 2026)
The catalytic subunit The catalytic subunit (P110α) of the phosphatidylinositol-4,5-bisphosphate 3-kinase (PI3K), which is encoded by PI3KCA gene located in chromosome 3, has been found to be upregulated significantly in patients with breast cancer. The research aims to study single nucleotide polymorphisms (SNP rs2108429654) located in exon 20. This SNP (rs2108429654) was genotyped in 70 women with breast cancer (50 postmenopausal and 20 premenopausal) and 40 control women using the DNA sequencing technique (Sanger method). According to statistical analysis of hormone receptors, prostaglandin hormone (PR), estrogen hormone (ER), and human epidermal growth factor receptor 2 hormones (HER-2) with menopausal status in patients with breast cancer show there were no significant differences. Isolated DNA is used to perform polymerase chain reaction (PCR) followed by DNA sequencing. The gene expression of PIK3CA was also determined by converting mRNA into cDNA via a reverse transcription mechanism, which will be used later in qPCR. The results of genotypic analysis of rs (2108429654) for AA genotype (OR= 1.0), AT genotype (OR= 0.1500, p= 0.0021), and TT genotype (OR= 0.2344, p= 0.0039) were significant associations with increased risk of BC. The median gene expression of PIK3CAwas (32.52) in patients increased significantly (p= 0.001) compared to control women (30.97) with expression fold for patients (3.525). All genotypes (AA, TT, and AT) of the SNP rs 2108429654 represent a high level of gene expression in patients compared to controls.